Prevalensi Ektoparasit yang Menyerang Benih Ikan Koi (Cyprinus carpio) di Bursa Ikan Hias Surabaya [The Prevalence Of Ectoparasits That Attack The Seed Of Koi Fish In The Stock Of Ornamental Fish Surabaya] - Sri Subekti; Novy Prasetya; Kismiyati Kismiyati (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract As the commodity grown, ornamental fish has an interesting added value. Many things can serve as a supporting factor in conducting the business of ornamental fish, such as having economic value and many enthusiasts who already spread to the whole society. One major problem in the cultivation of ornamental fish in Indonesia to this day is about the disease. One of the diseases that often strike in the ornamental fish pond is parasiter disease. In anticipation of losses due to parasitic attacks on fish, is necessary to identify types of ectoparasites that attack the seed of koi fish. This is done sejal early, so that the seeds are already carrying the disease agent could negatively impact on the enlargement and not widespread. The purpose of this study was to determine the type of ectoparasites that attack koi fish and find out the prevalence of ectoparasites that attack koi fish (Cyprinus carpio) in East Java at Prapen Surabaya The method used is a survey method for gathering informationfrom most of the population is considered to represent a particular population. Types of ectoparasites found were Trichodina sp., Chilodonella sp., Myxobollus sp., Ichtyopthirius multifilis, Dactylogyrus sp, Gyrodactylus sp., And Argulus japonicus. Prevalence rate of ectoparasites that infested fish Koi (Cyprinus carpio) in Surabaya fish stock is Trichodina sp. 84%, Chilodonella sp. 31%, Myxobollus sp. 17%, Ichtyopthirius multifilis 4%, 13% Dactylogyrus sp., Gyrodactylus sp. 7% and Argulus sp. 14%.